Beyond Language. The Semiotics of Marginal Foods - Fazioni, Nicolò (E|C, 2025)
This paper seeks to explore, through the lens of semiotics, the narrative of “strange foods” as a constitutive element in the construction of the “other’s” identity. We will examine the symbolic spaces where power structures regulate the movement of “other foods,” their marginalized communal sharing, or their rhizomatic proliferation in distinctive urban areas (such as Queens). We will analyze a range of texts and images, spanning from international regulatory legislation to social media campaigns by populist parties, to reconstruct the modalities through which foods originating from external sources (immigrant foods, novel foods) are signified and regulated within the EU and US contexts. We conclude by engaging with Deleuze’s (1969) exploration of the relationship between eating and speaking, illustrating the connections between linguistic practices and food consumption. Building on this idea, we will explore why discussions of the “other”, the enemy frequently begin with the characterization of their language – foreign sounds – and extend to their “strange” food.